Efektivitas Pijat Woolwich Dan Teknik Marmet Terhadap Kelancarkan Produksi Asi Pada Ibu Post Partum - Purwandari, Atik; Lontaan, Anita; Albar, Fadilah; Korompis, Martha Deborah; Tuju, Sjenny Olga; Tombokan, Sandra; Fajrin, Irmasanti; Novitasari, Anis; Losu, Fredrika Nancy; Dompas, Robin; Tahulending, Anneke (POLTEKKES KEMENKES MANADO, 2023)
Background: massage woolwich and the marmet technique is a way of massaging and expressing milk to stimulate the hormones prolactin and oxytocin in the mother after giving birth so that milk production can be launched. The author is interested in doing research with the title of massage effectiveness woolwich and the marmet technique on the smoothness of breast milk production in postpartum mothers. Objective: This research aims to examine literature, articles, and research documents identifying the effectiveness of Massagewoolwich and the marmet technique for smooth milk production in postpartum mothers. Method: The type of research in this study is metadata analysis using a literature review about the effectiveness of massage woolwich and the marmet technique for smooth milk production in postpartum mothers. Searching for research articles in several databases using certain keywords from 2015 to 2020. The search results obtained 8 articles that meet the criteria, so it is good to analyze further. Critical analysis of 8 articles was done based on design, population and sample, treatment, parameters, findings, and conclusions. Results: The literature review in the article it was found the effectiveness of massage woolwich and marmet technique to facilitate breast milk production in postpartum mothers. Each treatment showed significant changes with massage woolwich and the marmet technique can increase the smoothness of breast milk production in postpartum mothers.